Treatment of acute gastroduodenal stress ulcers - Cazabán, Luis A; Carriquiry, Luis; Baldizán, Jorge W (Cirugía del Uruguay, 1977)
The authors define anatomical, clinical and pathogenic characteristics of acute gastroduodenal stress ulcers. The paper contains a review of existing bibliography, in the light of which are established, guidelines for its treatment urgency surgery is required for improving results.